Effect of Biochar Addition on Phosphorus Adsorption Characteristics of Red Soil - Wu, Yunchao; Zou, Ziwei; Huang, Chenxu; Jin, Jie (Frontiers in Environmental Science, 2022)
Phosphorus (P) sorption by red soil is strong due to its acidic pH and high content of metal oxides. Biochar addition may increase the availability of red soil P by altering P sorption characteristics. This study examined the influences of doping ratio of biochar, phosphate concentration, solution pH, and biochar-derived dissolved black carbon (DBC) on P sorption by a red soil. The specific sorption mechanisms were explored using 3D fluorescence spectroscopy, infrared spectroscopy, and zeta potential analysis. The results show that the bioavailable P content in the biochar-amended red soil rose to 1.92 mg∙kg-1, which is an increase of 255% compared with the original red soil. With the increase in the doping ratio of biochar, the maximum sorption amount of P initially decreased and then increased. Moreover, the pH value and the content of the dissolved organic carbon (DOC) of the red soil were effectively elevated by biochar addition. The increase in DOC content is likely caused by the DBC released from biochar. As the soil pH value increased, the amount of P sorption was reduced due to electrostatic repulsion. P sorption by the red soil decreased with increasing DBC concentration. The humic acid-like substances in DBC can compete with phosphate for soil sorption sites, leading to the decrease in P absorption. This study demonstrates that the addition of biochar affects P sorption of the red soil mainly by changing its physicochemical properties or by releasing DBC to occupy the sorption sites.